The Effect of the Quality of General Administrative Services on Student Satisfaction of the Study Program of Nursing STIKes Sukabumi - Ristianti Meidara; Rizki Hegia Sampurna; M. Rijal Amirulloh (Budapest International Research and Critics University, 2022)
National development is a series of sustainable development efforts and covers all aspects of community, nation, and state life. Higher education institutions as one of the service managers must also take into account the level of student satisfaction in order to be able to carry out lecture activities properly. Service quality in the field of education is one of the factors that determine the selection of something that can satisfy users, one of which is students. The success of an institution is largely determined by the quality of the services provided. The purpose of this study was to determine the effect of the quality of general administration services on student satisfaction in the Nursing Undergraduate Study Program of STIKes Sukabumi. Research Methods: Correlational research with a cross sectional approach. The population is all active students of Level 4 Semester VIII of the STIKes Nursing Undergraduate Study Program as many as 116 with a total sample of 90 respondents. Sampling technique using stratified random sampling with statistical correlation test analysisSperman Rank. Research result: The results of statistical tests using Spearman correlation obtained p value = 0.000 <0.05. The correlation value of 0.652 is in the correlation index range of 0.60 – 0.79 so that the influence of the quality of administrative services on student satisfaction has a strong relationship. Conclusion: There is an influence of the quality of general administration services on student satisfaction of the Bachelor of Nursing Study Program STIKes Sukabumi.